Testing the Steve Jobs Hypothesis in a B2B Context: Will a Portfolio of Hierarchically Related Technology Products Improve Customer Outcomes?. (August 2013) - Kuruzovich, Jason; Han, Shu; Koukova, Nevena T.; Ravichandran, T.
This research examines how the type of information technology (IT) provided among hardware, software, and services—and the degree to which the IT provided is bundled into a solution—influences the levels of satisfaction and loyalty of IT buyers. We refer to the hardware, software, and services offerings jointly as the IT products-services stack, as technology stacks are useful visualizations of how layers of technology products are hierarchically related. We utilize over 36, 000 ratings of 68 IT vendors provided by the vendors' customers to test our research model. The findings indicate that vendors offering products in the lower levels of the IT products-services stack experience higher satisfaction and loyalty ratings (hardware > software > services). Moreover, satisfaction and loyalty ratings are highest when hardware, software, and services are provided together—that is, as an IT solution. An important implication of these findings is that IT solutions benefit both vendors and buyers.